A new genus of Neotropical oak gall wasp, Prokius Nieves-Aldrey, Medianero & Nicholls, gen. nov. (Hymenoptera: Cynipidae: Cynipini), with description of two new species from Panama - Medianero, Enrique; Nicholls, James A.; Stone, Graham N.; Nieves-Aldrey, José Luis (Zootaxa, 2021)
A new genus, Prokius Nieves Aldrey, Medianero & Nicholls, gen. nov., and two new species of oak gall wasps (Hymenoptera: Cynipidae: Cynipini), Prokius cambrai Medianero & Nieves-Aldrey sp. nov. and Prokius lisethiae Medianero & Nieves-Aldrey sp. nov., are described from adults reared from galls on Quercus bumelioides Liebm (Fagaceae, sect. Quercus, white oaks) collected in Panama. The new genus is phylogenetically and morphologically close to Dros Kinsey and forms part of a large clade that includes species from several other genera that appear to require revision, including Andricus Hartig and Phylloteras Ashmead. Molecular and morphological data, diagnostic characters, gall descriptions, distribution and biological data of the new genus and the new species are given. This new genus represents the fourth recently described genus of Cynipidae endemic to the Neotropical region.